Sistem Pendukung Keputusan Pemilihan Berita Online Yang Akan Terbit Pada Perusahaan Media Online PT. Zaki Angkasa Hamdani Dengan Menerapkan Metode Profile Matching - Okataviandi, Rio (Jurnal Kajian Ilmiah Teknologi Informasi dan Komputer, 2023)
Online news selection is the activity of selecting several news stories by assessing each news item based on existing criteria, this process is carried out by the Editor-in-Chief. News that is interesting and has high value will be placed at the front and become the main news. Packaging in news media has its own appeal, because it will attract people to read news in each news media. Inaccuracy in selecting online news and the length of the news selection process. So the online news that is published often does not provide accurate information, and can have a negative impact on readers. Based on the problems above, a decision support system will be built to determine the selection of online news that will be published using the Profile Matching method. In this research, the Profile Matching method is applied with the aim of providing the best solution in determining the selection of online news that will be published on PT. Zaki Angkasa Hamdani. Based on the criteria set by PT. Zaki Angkasa Hamdani used in this research, namely: News Title, News Writing, Data Completeness and Data Quality. This aims to make it easier to determine priorities for selecting online news that will be published more quickly and accurately so that later it can be more helpful to PT. Zaki Angkasa Hamdani in determining the selection of online news that will be published on PT. Zaki Angkasa Hamdani. Based on the results obtained from the ranking value for the selection of online news that will be published, there is a news with the title Pegasus Pancur Batu Police Ringkus HP Robber (A2) with a value of 6,964, so it can be proposed as online news that will be published based on the results of the selection that has been carried out.